Anatomopathological and molecular studies of Marek´s disease virus in India - Visnuvinayagam, Sivam; Dash, Bana B.; Barathidasan, Rajamani; Mayilkumar, Kuppusamy; Selvaraju, Ganapathy (Brazilian Journal of Veterinary Pathology, 2019)
In India, increasing incidence of Marek’s Disease Virus (MDV) outbreaks are being reported even in vaccinated poultry farms. Hence identifying the new emerging pathotype of MDV is necessary for successful control through vaccination. Birds received in the post mortem section of The Avian Disease Laboratory, Indian Veterinary Research Institute, were screened for the presence of MDV by collecting neoplastic tissues, spleen and feather follicles. Screening was carried out by polymerase chain reaction (PCR) and histopathological examination. Among the tested 150 birds’ tissue samples, 35 bird tissue samples were found positive for MDV. Based on pathotyping specific PCR, it was found that 34 birds tissues were affected virulent MDV and one birds tissue was affected with very virulent MDV. Since, HVT vaccine will not protect the very virulent pathotype, combined vaccine of SB-1 and HVT can be administered to control the very virulent MDV. Among the MD infected birds, neoplastic liver is most commonly encountered. Spleen tissue samples was found to be more suitable for the DNA isolation for PCR.